Modelling of charge-exchange induced NBI losses in the COMPASS upgrade tokamak. (8th March 2021) - Jaulmes, F.; Zadvitskiy, G.; Bogar, K.; Imrisek, M.; Hromadka, J.; Cats, S.Y.; Varju, J.; Komm, M.; Panek, R.
Abstract: The COMPASS upgrade tokamak (Panek et al 2017 Fusion Eng. Des. 123 11–16) will be a tokamak of major radius R 0 = 0.894 m with the possibility to reach high field ( B t ∼ 5 T) and high current ( I p ∼ 2 MA). The machine should see its first plasma in 2023 and H-mode plasma will be obtained from 2025. The main auxiliary heating system used to access H-mode will be 4 MW of neutral beam injection (NBI) power. The NBI will have a nominal injection energy of 80 keV, a maximum injection radius R tan = 0.65 m and will create a population of well-confined energetic D ions. In this contribution, our modelling studies the NBI deposition and losses when a significant edge background density of neutrals is assumed. We follow the fast ions in the 3D field generated by the 16 toroidal field (TF) coils using the upgraded EBdyna orbit solver (Jaulmes et al 2014 Nucl. Fusion 54 104013). We have implemented a Coulomb collision operator similar to that of NUBEAM (Goldston et al 1981 J. Comput. Phys. 43 61) and a charge-exchange operator that follows neutrals and allows for multiple re-ionizations. Detailed integrated modelling with the METIS code (Artaud et al 2018 Nucl. Fusion 58 105001) yields the pressure and current profiles for various sets of achievable engineering parameters. The FIESTA code (Cunningham 2013 Fusion Eng. Des. 88 3238–3247) calculates the equilibrium and a Biot–Savart solver is used to calculate the intensity of the perturbation induced by the TF coils. Initial distributions of the NBI born fast ions are obtained from the newly developed NUR code, based on Suzuki et al (1998 Plasma Phys. Control. Fusion 40 2097). We evolve the NBI ions during the complete thermalization process and we calculate the amount of NBI ions loss in the edge region due to neutralizations. Results indicate the NBI losses for various injection geometries, various engineering parameters and various assumptions on the magnitude of the background neutral densities.